Evaluation of temefos and pyriproxyfen to control Aedes aegypti larvae in laboratory conditions - Pérez, María (2017)
Objective: To evaluate the efficacy of temefos versus pyriproxyfen at different doses (0.01, 0.02, 0.03, 0.04 and 0.05 ppb) to control Aedes aegypti larvae in laboratory conditions. Materials and methods: An experimental study with control group which included 2,000 Aedes aegypti larvae from the Collique III Zona jurisdiction in Comas, Peru, and the Rockefeller strain as susceptible control. The difference in the time of onset of the larvicidal effect was established. Additionally, the survival and mortality rates with temefos versus pyriproxyfen were evaluated at different doses (0.01, 0.02, 0.03, 0.04 and 0.05 ppb) in laboratory conditions using the methodology recommended by the World Health Organization (WHO). Results: Based on the results, the Collique III Zona strain larvae exposed to temefos showed an average mortality rate of 68.4%, as opposed to the average mortality rate in the pyriproxyfen assay, which was 0.8%. Regarding the Rockefeller strain exposed to temefos, the average mortality rate was 100%, as opposed to the average mortality rate in the pyriproxyfen assay, which was 0.8%. This indicates that temefos has a faster larvicidal effect to control Aedes aegypti larvae. Conclusions: The Aedes aegypti larvae population was susceptible to insecticide temefos. A single application of temefos at 0.04 ppm showed a mortality rate of 92% in the larvae. With insect growth regulator pyriproxyfen, very low mortality rates were found in the Collique and Rockefeller strains.